Optimalisasi Pemanfaatan Lahan Pekarangan melalui Program P2L pada KWT Akur di Desa Kawunganten Kecamatan Cikaum Kabupaten Subang - lusiana priyatna; Tita Kartika Dewi; Hamdan Drian; Nine Wahyuni; Vera Purnama (Universitas Majalengka, 2023)
Abstract Sustainable Food Courts (P2L) is an activity of utilizing yards as a source of food in a sustainable manner to increase the availability, accessibility, use and income of the community. P2L is a government program in dealing with food insecurity. Optimization of P2L by empowering women in the use of yards as a source of family food by cultivating various types of vegetable and medicinal plants as additional food availability. P2L aims to empower women farmers (KWT) to have knowledge, skills, motivation in utilizing the yard as a source of food and family income and being able to carry out environmentally friendly and economical plant cultivation through conventional and simple hydroponic plant cultivation systems. The method used is group participation involving the community in activities: counseling, training and mentoring. In the cultivation practice, participants were given knowledge about preparing planting media, seeding and planting. The activity begins with the practice of preparing good planting media for vegetable crops. In this activity group members were able to prepare planting media with good media composition. KWT Akur members are generally skilled in plant cultivation practices. KWT Akur is very enthusiastic about P2L activities and is very skilled in good plant cultivation practices. The motivation of KWT Akur members needs to be increased through regular assistance by optimizing activities and support from the Subang District Food Security Service. P2L in KWT Akur, is expected to improve the economy and use of yards as a provider of food sources and household nutrition Keywords: yard land; Food security; Food; sustainable Abstrak Pekarangan Pangan Lestari (P2L) merupakan kegiatan pemanfaatan lahan pekarangan sebagai sumber pangan secara berkelanjutan untuk meningkatan ketersediaan, aksesibilitas, pemanfaatan dan pendapatan masyarakat. P2L adalah program pemerintah dalam penanganan rawan pangan.Optimalisasi P2L dengan memberdayakan wanita dalam pemanfaatan pekarangan sebagai sumber pangan keluarga dengan membudidayakan berbagai jenis tanaman sayuran dan obat sebagai tambahan ketersediaan pangan.P2L bertujuan untuk memberdayakan wanita Tani (KWT) agar memiliki pengetahuan,ketrampilan,memotivasi dalam memanfaatkan lahan pekarangan sebagai sumber pangan dan pendapatan keluarga serta dapat melaksanakan budidaya tanaman ramah lingkungan dan ekonomis melalui sistem budidaya tanaman konvensional dan hidroponik sederhana. Metode yang digunakan adalah partisipasi kelompok yang melibatkan masyarakat dalam kegiatan: penyuluhan, pelatihan dan pendampingan. Pada praktek budidaya peserta diberikan pengetahuan tentang persiapan media tanam,penyemaian dan penanaman. Kegiatan dimulai dengan praktek persiapan media tanam yang baik untuk tanaman sayuran. Pada kegiatan ini anggota kelompok mampu menyiapkan media tanam dengan komposisi media yang baik. Anggota KWT Akur umumnya terampil dalam praktek budidaya tanaman. KWT Akur sangat antusias dalam kegiatan P2L dan sangat terampil dalam praktek budidaya tanaman dengan baik. Motivasi anggota KWT Akur perlu ditingkatkan melalui pendampingan secara berkala dengan mengoptimalkan kegiatan dan dukungan dari Dinas Ketahanan Pangan Kabupaten Subang. P2L di KWT Akur,diharapkan dapat meningkatkan perekonomian serta pemanfaatan lahan pekarangan sebagai penyedia sumber pangan dan gizi rumah tangga Kata Kunci: lahan pekarangan; Ketahanan pangan; Pangan; Lestari Accepted: yyyy-mm-dd Published: yyyy-mm-dd